2011
DOI: 10.1351/pac-rep-07-09-39
|View full text |Cite
|
Sign up to set email alerts
|

Metrological traceability of measurement results in chemistry: Concepts and implementation (IUPAC Technical Report)

Abstract: This IUPAC study aims at formulating recommendations concerning the metrological traceability of a measurement result in chemistry. It is intended to provide the chemical measurement community with a consistent view of the creation, meaning, and role of metrological traceability and its underpinning concepts. No distinction is made between measurement results obtained in "high metrology" and in the "field". A description is given of the calibration hierarchies needed in different circumstances to arrive at met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
97
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(98 citation statements)
references
References 21 publications
0
97
0
1
Order By: Relevance
“…Metrological traceability scheme for qNMR According to De Bièvre et al [16], a metrological traceability scheme as shown in Fig. 1 can be drawn.…”
Section: Resultsmentioning
confidence: 99%
“…Metrological traceability scheme for qNMR According to De Bièvre et al [16], a metrological traceability scheme as shown in Fig. 1 can be drawn.…”
Section: Resultsmentioning
confidence: 99%
“…Since the value of this term is invariant among the participants of each KC, all measurement-specific factors that affect the pa 0 affect the corresponding pH values (as well as any KCRV calculated from them) to the same extent. The uncertainty [15] Note that primary pH is a procedurally defined kind-ofquantity [19]. Since primary pH cannot be determined except through the measurement process itself, the KCRV for a primary pH KC must be estimated from the measurement results even though the study materials are prepared quantitatively from materials of established composition.…”
Section: Primary Methods Ph Measurementsmentioning
confidence: 99%
“…The metrological chain of measurement starts with a preparation of a primary calibrator (standard) with an assigned property value [8]. This is then used to calibrate the measuring system.…”
Section: Calibrationmentioning
confidence: 99%